2002
DOI: 10.1002/jmor.10039
|View full text |Cite
|
Sign up to set email alerts
|

Specialized mucous glands and their possible adaptive role in the males of some species of rana (amphibia, anura)

Abstract: A structural and ultrastructural study was carried out on the cutaneous glands in some species of Rana (R. dalmatina, R. iberica, R. italica, R. "esculenta," and R. perezi), giving particular attention to the mucous secretory units. Two different types of mucous glands occur in R. dalmatina, R. iberica, and R. italica. Besides the ordinary mucous units, which are randomly distributed over the body surface in both males and females, a further population of mucous glands was observed on the male dorsal skin. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 34 publications
5
52
1
7
Order By: Relevance
“…Mucous glands are typically small and widely distributed over the body and produce an acidic secretion containing carbohydrates (Fontana et al, 2006). Substances in the mucus can attract bacteria and fungi, which can be a food source for these microorganisms (Ducklow and Michell, 1979;Duellman and Trueb, 1986;Brizzi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Mucous glands are typically small and widely distributed over the body and produce an acidic secretion containing carbohydrates (Fontana et al, 2006). Substances in the mucus can attract bacteria and fungi, which can be a food source for these microorganisms (Ducklow and Michell, 1979;Duellman and Trueb, 1986;Brizzi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The present morphological study revealed that the skin glands of T. karelinii are different in some aspects from those of the other anuran amphibians (Staub & Paladin 1997;Delfino et al 1999;Brizzi et al 2002). Serous glands of T. karelinii show large alveoli and are more numerous in dorsal skin when compared to ventral skin.…”
Section: Discussionmentioning
confidence: 53%
“…In typical mucous glands, secretory epithelium consists of low prismatic or cubic cells limiting large lumen containing non-granular or vesicular secretory material. In addition, the diameter of these glands is smaller than that of serous glands (Dapson 1970;Dominguez et al 1981;Brizzi et al 2002), which is common in amphibians. In T. karelinii, we determined two types of mucous glands according to their morphology and histochemical affinity.…”
Section: Discussionmentioning
confidence: 98%
“…However, the majority of the anuran species have not had their gland content examined by science and so remain unknown. The cutaneous gland ultrastructural characterization of all living amphibians demonstrates that they usually belong to four main types located in the spongious dermis differing from others in size and secretory activity, and can be classified as: mucous, serous (granular or poison), lipid (or wax), and mixed (seromucous) glands (Almeida et al, 2007;Brizzi et al, 2002;Duellmann & Trueb, 1994;Lacombe et al, 2000). Each gland presents specific action in homeostasis behavior: lipid glands promote the impermeabilization of the skin in order to decrease water loss (Castanho & De Luca, 2001); mucous glands produce mucus to support cutaneous functions, such as respiration, reproduction, thermoregulation, and defence (Toledo & Jared, 1995); serous glands, that are the largest and most widely distributed over the animal's body surface, act as a main element in amphibian passive chemical defence (Lacombe et al, 2000;Toledo & Jared, 1995).…”
Section: Anuran Skin Protective Adaptationsmentioning
confidence: 99%